Does gender moderates the relationship between favoritism/nepotism, supervisor incivility, cynicism and workplace withdrawal: A neural network and SEM approach - Abubakar, A. Mohammed; Namin, Boshra Hejraty; Harazneh, Ibrahim; Arasli, Huseyin; Tunc, Tugba (Elsevier, 2017)
Organizational politics and workplace victimization are social stressors with significant implications on the wellbeing of employees. Applying Job Demand Resources framework, this study examines the impact of favoritism/nepotism, supervisor incivility on employee cynicism, and work withdrawal, and the moderating role of gender. Utilizing a cross-sectional design, data were gathered from frontline employees working in 3-star hotels in Northern Cyprus. Results from structural equation modeling and artificial neural network revealed that: (1) favoritism/nepotism has a positive impact on employee cynicism and work withdrawal; (2) employee cynicism has a positive impact on work withdrawal; (3) employee cynicism mediates the relationship between favoritism/nepotism, and work withdrawal; (4) the impact of employee cynicism on work withdrawal was about 6.7 times stronger for women; (5) the impact of favoritism/nepotismon work withdrawal was about 2.1 times stronger for men. Strategies to reduce this unwanted practices and how to keep employees productive are discussed. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Favoritism/nepotism; Employee cynicism; Supervisor incivility; Gender; Work withdrawal; Northern Cyprus